Uninvited office visits: Supervising students in uncharted territories and orphaned contexts - Anthony Kambi Masha; Nana Yaw Brenya Agyeman (Himpunan Pengembang Kurikulum Indonesia, 2025)
Much of the focus on doctoral success emphasizes the epistemological aspects of the doctoral process that prioritize the doctoral candidate. However, since both the supervisor and the candidate play important roles in the supervision process, more research is needed to recognize supervisors' efforts toward the success of postgraduate students. Therefore, this study examines the perspectives of supervisors who implement effective supervisory practices while guiding PhD students, who often navigate unfamiliar territory and may feel unsupported. The study employed a case study design using a qualitative approach, targeting four doctoral supervisors from a university in the Eastern Cape province of South Africa. Purposive sampling was utilized to select these participants. In-depth interviews were conducted to gather their insights, and the data were analyzed through narrative analysis, with responses recorded verbatim following the research questions. The findings indicated that guiding students during supervision is crucial for effective supervisory practices. The study recommends that supervisors actively engage in the supervisory process to foster a positive relationship with their students. Ultimately, it concludes that supervisors need to adopt key practices during supervision, acknowledging the significance of their actions in helping students become knowledge producers. Abstrak Sebagian besar fokus pada keberhasilan doktoral menekankan aspek epistemologis dari proses doktoral yang memprioritaskan kandidat doktoral. Namun, karena baik supervisor maupun kandidat memainkan peran penting dalam proses pengawasan, penelitian lebih lanjut diperlukan untuk mengakui upaya yang dilakukan supervisor terhadap keberhasilan mahasiswa pascasarjana. Oleh karena itu, penelitian ini memeriksa perspektif supervisor yang menerapkan praktik pengawasan yang efektif sambil membimbing mahasiswa PhD, yang seringkali menavigasi wilayah yang tidak dikenal dan mungkin merasa tidak didukung. Penelitian ini menggunakan desain studi kasus dengan pendekatan kualitatif, menargetkan empat supervisor doktoral dari sebuah universitas di provinsi Eastern Cape, Afrika Selatan. Sampling bertujuan digunakan untuk memilih peserta ini. Wawancara mendalam dilakukan untuk mengumpulkan wawasan mereka, dan data dianalisis melalui analisis naratif, dengan tanggapan dicatat secara verbatim sesuai dengan pertanyaan penelitian. Temuan menunjukkan bahwa membimbing mahasiswa selama proses pengawasan sangat penting untuk praktik pengawasan yang efektif. Penelitian ini merekomendasikan agar supervisor secara aktif terlibat dalam proses pengawasan untuk memupuk hubungan positif dengan mahasiswa mereka. Pada akhirnya, disimpulkan bahwa supervisor perlu mengadopsi praktik-praktik kunci selama pengawasan, mengakui pentingnya tindakan mereka dalam membantu mahasiswa menjadi produsen pengetahuan. Kata kunci: institusi pendidikan tinggi; pascasarjana; penelitian; pengawasan; supervisor